Social Support Moderates Effects of Natural Disaster Exposure on Depression and Posttraumatic Stress Disorder Symptoms: Effects for Displaced and Nondisplaced Residents - McGuire, Adam P.; Gauthier, Jami M.; Anderson, Lisa M.; Hollingsworth, David W.; Tracy, Melissa; Galea, Sandro; Coffey, Scott F. (Journal of traumatic stress, 2018)
Social support is a known protective factor against the negative psychological impact of natural disasters. Most past research has examined how the effects of exposure to traumatic events influences whether someone meets diagnostic criteria for depression and posttraumatic stress disorder (PTSD); it has also suggested sequelae of disaster exposure depends on whether survivors are displaced from their homes. To capture the full range of the psychological impact of natural disasters, we examined the buffering effects of social support on depressive symptoms and cluster‐specific PTSD symptoms, with consideration of displacement status. In a survey conducted 18 to 24 months after Hurricane Katrina, 810 adults exposed to the disaster reported the number of Katrina‐related traumatic events experienced, perceived social support 2 months post‐Katrina, and cluster‐specific PTSD and depressive symptoms experienced since Katrina. Analyses assessed the moderating effects of social support and displacement and the conditional effects of displacement status. Social support significantly buffered the negative effect of Katrina‐related traumatic events on depressive symptoms, B = −0.10, p = .001, and avoidance and arousal PTSD symptoms, B = −0.02, p = .035 and B = −0.02, p = .042, respectively. Three‐way interactions were nonsignificant. Conditional effects indicated social support buffered development of depressive symptoms across all residents; however, the moderating effects of support on avoidance and arousal symptoms only appeared significant for nondisplaced residents. Results highlight the protective effects of disaster‐related social support among nondisplaced individuals, and suggest displaced individuals may require more formal supports for PTSD symptom reduction following a natural disaster. Resumen Spanish s by the Asociación Chilena de Estrés Traumático (ACET) El Apoyo Social Modera los Efectos de la Exposición a Desastres Naturales sobre los Síntomas de Depresión y Trastorno de Estrés Postraumático: Efectos para Residentes Trasladados y No‐Trasladados APOYO SOCIAL MODERA LOS EFECTOS DE LOS DESASTRES NATURALES El apoyo social es un factor protector conocido contra el impacto psicológico negativo de los desastres naturales. La mayoría de la investigación previa ha examinado cómo la exposición a eventos traumáticos influencia la posibilidad de cumplir los criterios diagnósticos para depresión y trastorno de estrés postraumático (TEPT); también se ha sugerido que las secuelas de la exposición a desastres dependen de si los sobrevivientes son trasladados de sus hogares. Para capturar el rango completo del impacto psicológico de los desastres naturales, examinamos los efectos de amortiguadores que ejerce el apoyo social en síntomas depresivos y los dominios sintomáticos dentro del TEPT, considerando el estado de Trasladado o No‐Trasladado. En una encuesta realizada 18 a 24 meses tras el huracán Katrina, 810 adultos expuestos a ese desastre reportaron el número de eventos traumáticos experimentados relacionados con Katrina, apoyo social percibido dos meses después de Katrina, y dominios sintomáticos de TEPT y síntomas de depresión sufridos desde Katrina. El análisis examinó los efectos moderadores del apoyo social y de la situación de traslado, así como los efectos condicionales del estatus de trasladado. El apoyo social mitigó significativamente los efectos negativos de los eventos traumáticos relacionados con Katrina en síntomas depresivos, B = ‐0.10, p = .001, así como los dominios sintomáticos de evitación e hiperactivación en TEPT (B = ‐0.02, p = .035 y B = ‐0.02, p = .042, respectivamente). Las interacciones en tres direcciones fueron no significativas. Los efectos condicionales mostraron que el apoyo social amortiguó el desarrollo de síntomas depresivos en todos los individuos; sin embargo, los efectos moderadores del apoyo sobre los síntomas de evitación e hiperactivación sólo alcanzaron significancia para personas no‐trasladadas. Estos resultados enfatizan los efectos protectores del apoyo social en desastres en individuos no trasladados, y sugieren que individuos trasladados podrían requerir apoyos más formales para reducir los síntomas de TEPT después de un desastre natural. 抽象 Traditional and Simplified Chinese s by AsianSTSS Social Support Moderates Effects of Natural Disaster Exposure on Depression and PTSD Symptoms: Effects for Displaced and Non‐Displaced Residents Traditional Chinese 標題: 社會支持會調節天災經歷對抑鬱症及PTSD症狀的影響:在有和無跟家園分離的人的效應 撮要: 我們已知社會支持是天災導致的負面心理影響的保護因素。過往大部分研究亦檢視創傷經歷怎樣影響當事人是否符合患抑鬱症和創傷後壓力症(PTSD)的標準;亦指出天災經歷的後遺症如何, 視乎生還者是否跟家園分離。為了解天災構成的全面心理影響, 本研究檢視社會支持對於抑鬱症狀及PTSD症狀的特殊聚類構成的緩衝效應, 亦考慮到樣本與家園分離的狀況。在颶風卡特里娜發生18 至24月後, 810名經歷此天災的成人接受調查, 報告了他們經歷與此颶風相關的創傷事件數目、颶風發生兩個月後的社會支持感知、以及他們在颶風後的PTSD特殊症狀聚類和抑鬱症狀。我們分析社會支持及跟家園分離產生的調節效應, 以及跟家園分離的狀況產生的制約效應。社會支持顯著地緩衝了與颶風卡特里娜相關的創傷事件對抑鬱症狀(B = ‐0.10, p = .001)、和PTSD裡的迴避與警覺症狀(分別為B = ‐0.02, p = .035 與B = ‐0.02, p = .042)構成的負面影響。三向的交互作用並不顯著。制約效應反映, 在所有居民中社會支持都緩衝了抑鬱症狀的發展。然而, 社會支持對迴避和警覺症狀的調節效應, 卻只在沒與家園分離的樣本中顯著。結果凸顯出天災相關的社會支持對沒與家園分離的人產生保護效應, 並反映與家園分離的人可能需要更多專業支持, 以減輕天災後的PTSD症狀。 Simplified Chinese 标题: 社会支持会调节天灾经历对抑郁症及PTSD症状的影响:在有和无跟家园分离的人的效应 撮要: 我们已知社会支持是天灾导致的负面心理影响的保护因素。过往大部分研究亦检视创伤经历怎样影响当事人是否符合患抑郁症和创伤后压力症(PTSD)的标准;亦指出天灾经历的后遗症如何, 视乎生还者是否跟家园分离。为了解天灾构成的全面心理影响, 本研究检视社会支持对于抑郁症状及PTSD症状的特殊聚类构成的缓冲效应, 亦考虑到样本与家园分离的状况。在飓风卡特里娜发生18 至24月后, 810名经历此天灾的成人接受调查, 报告了他们经历与此飓风相关的创伤事件数目、飓风发生两个月后的社会支持感知、以及他们在飓风后的PTSD特殊症状聚类和抑郁症状。我们分析社会支持及跟家园分离产生的调节效应, 以及跟家园分离的状况产生的制约效应。社会支持显著地缓冲了与飓风卡特里娜相关的创伤事件对抑郁症状(B = ‐0.10, p = .001)、和PTSD里的回避与警觉症状(分别为B = ‐0.02, p = .035 与B = ‐0.02, p = .042)构成的负面影响。三向的交互作用并不显著。制约效应反映, 在所有居民中社会支持都缓冲了抑郁症状的发展。然而, 社会支持对回避和警觉症状的调节效应, 却只在没与家园分离的样本中显著。结果凸显出天灾相关的社会支持对没与家园分离的人产生保护效应, 并反映与家园分离的人可能需要更多专业支持, 以减轻天灾后的PTSD症状。